DEVELOPING RELIGIOUS BEHAVIOR BASED ON HADITH IN EARLY CHILDHOOD EDUCATION INSTITUTIONS - Pamuji, Zuri (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2024)
The introduction of hadith-based adab can influence a person’s religious behavior, including in early childhood. This research attempts to describe in depth the efforts of teachers in early childhood education institutions in developing religious behavior based on the hadith of the Prophet. This research uses the living hadith method, especially practical studies regarding Muslim social phenomena related to hadith texts. The research location is KB Al-Azkia Purwokerto which consistently teaches adab, one of the sources of which is hadith. Data collection at the location was carried out through interviews, documentation, and observation, and was complemented by a study of hadiths related to the phenomenon. The research results show that: first, the hadith that is used as a teacher in developing religious behavior is a hadith related to drinking etiquette, namely the hadith of Muslim history no. 2026 and this hadith is of authentic quality. Second, the teacher’s efforts to build hadith-based religious behavior are carried out through three stages, namely: introducing, training, and getting used to. The process of implementing these three stages is carried out by paying attention to the age development and potential of students, especially in the aspects of religion and morals, cognitive, language, and social-emotional. The results of the implementation show that students are getting to know the etiquette of drinking while sitting, dare to practice, and have the courage to tell the teacher if other students need to follow the etiquette that has been taught.[Pengenalan adab berbasis hadis dapat berpengaruh pada perilaku keberagamaan seseorang, termasuk pada anak usia dini. Penelitian ini berupaya mendeskripsikan secara mendalam bagaimana usaha dari guru di lembaga pendidikan anak usia dini dalam membangun perilaku keagamaan berbasis hadis Nabi. Penelitian ini menggunakan metode living hadis khususnya studi praktik mengenai fenomena sosial muslim yang terkait dengan teks hadis. Lokasi penelitian di KB Al-Azkia Purwokerto yang secara konsisten mengajarkan adab, yang salah satu sumbernya adalah hadis. Penggalian data di lokasi dilakukan melalui wawancara, dokumentasi dan observasi, serta dilengkapi dengan mengkaji hadis yang berkaitan dengan fenomena. Hasil penelitian menunjukkan bahwa: pertama, hadis yang dijadikan guru dalam membangun perilaku keberagamaan merupakan hadis yang berkaitan dengan adab minum, yakni hadis riwayat muslim no 2026 dan hadis ini berkualitas shahih. Kedua, upaya guru dalam membangun perilku religius berbasis hadis dilakukan melalui tiga tahapan, yakni: mengenalkan, melatih dan membiasakan. Proses implementasi tiga tahapan tersebut dilakukan dengan memperhatikan perkembangan usia dan potensi peserta didik, khususnya pada aspek agama dan moral, kognitif, bahasa, serta sosial emosional. Hasil dari implementasi yang dilakukan menunjukkan bahwa siswa mulai kenal dengan adab minum sambil duduk, berani mempraktikkan serta berani memberitahukan kepada guru jika ada siswa lain yang tidak sesuai dengan adab yang telah diajarkan.]